Donkey skin - Barella, Laura (Swindon : Child's Play (International) Ltd, 2011)
A princess uses a gift from her father, a donkey skin, to conceal herself from her father's soldiers who come looking for her after she runs away.
Shelving Location Pop-up Books Section
Keywords: Fairy Tales